Chemical Bonds Visualization using Particle Effect and Augmented Reality - Christyowidiasmoro Christyowidiasmoro; Surya Sumpeno (Institut Teknologi Sepuluh Nopember, 2014)
Augmented Reality (AR) is a research area that allow to overlay multimedia contents such as text and visual information onto real world through camera views. AR can be used to as an educational assistance to help student acquire a deep conceptual understanding and spatial intuition. The course material can be enriched by viewing multimedia content, as well as in tabletop AR environment. We present this paper an AR system for teaching chemical problem solving especialy chemical bonds to highschool students. Our system is built based on inexpensive webcams and open-source library. Chemical bonds are visualize through marker. By combine different markers, student can get different result and visualization. A survey was conducted after experience the AR chemical bonds, show great acceptance of system and visualization.